Street Children Phenomenon in Makassar City : A Criminological Analysis - Nur Fadhilah Mappaselleng (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
The presence of children who live on the streets has caused concern in various cities in Indonesia, especially Makassar, South Sulawesi. Lack of education, decent life, and government attention trigger street children to do unlawful acts, such as drugs and drinking. From a criminological perspective, the phenomenon of street children can be explained using the social learning theory. Social learning theory is a convergence between differential association theory with general behavioural principles, which in this theory explains that criminal behaviour can be obtained from environmental influences. There is a reciprocal interaction that directs a person’s behaviour. This study aims to determine the description of street children’s existence in the city of Makassar, analyse the factors that cause the phenomenon of street children, and determine the prevention of street children. The research method uses a type of qualitative research sourced from the various scientific literature. This study indicates that the phenomenon of street children is a warning signalling the need for social development and poverty eradication policies to improve the situation on the broader community and prevent more young people from becoming marginalised. Every child must be protected according to United Nations Children’s Fund and also has been regulated in Regional Regulation No. 2 of 2008 concerning the Development of Street Children, Homeless, Beggars and Buskers in Makassar City